2015
DOI: 10.3390/su7078598
|View full text |Cite
|
Sign up to set email alerts
|

Social Impacts of GM Crops in Agriculture: A Systematic Literature Review

Abstract: It has recently been argued that the fragmented knowledge on the social impacts of genetically modified (GM) crops is contributing to the polarised debate on the matter. This paper addresses this issue by systematically reviewing 99 peer-reviewed journal articles published since 2004 on the social impacts of GM crops in agriculture; summarising current knowledge, and identifying research gaps. Economic impact studies currently dominate the literature and mainly report that GM crops provide economic benefits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 101 publications
(192 reference statements)
1
29
1
2
Order By: Relevance
“…The company invested significant resources in emerging markets in, e.g., Brazil, China, India and South Africa and started development programmes aimed at helping resource-poor farmers improve their food security and make their farming business-orientated [2,15]. It is notable that despite this significant attention to the developing world and small farmers, Monsanto's GM products remained mainly directed at large-scale, capital-intensive farmers [11,15,20].…”
Section: The Corporate Framing Of Gm Crops As Technology For the Poormentioning
confidence: 99%
See 1 more Smart Citation
“…The company invested significant resources in emerging markets in, e.g., Brazil, China, India and South Africa and started development programmes aimed at helping resource-poor farmers improve their food security and make their farming business-orientated [2,15]. It is notable that despite this significant attention to the developing world and small farmers, Monsanto's GM products remained mainly directed at large-scale, capital-intensive farmers [11,15,20].…”
Section: The Corporate Framing Of Gm Crops As Technology For the Poormentioning
confidence: 99%
“…Some have also claimed that the GM crops currently available on the market are developed for simplifying large-scale farming practices and are less suitable for resource-constrained smallholder practices [2]. The pro-GM literature and the emerging critique direct a significant amount of attention to the Global South, e.g., a recent review of the literature on the social impacts of GM crops in farming found that only four out of 99 studies on the issue had an empirical focus on the Global North [11]. Despite that Europe as a planted, has any significant commercial GM crop production (although still minimal in comparison with the countries listed above) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Japanese companies' incentives to invent GM crop technologies were relatively low compared to those of companies in other countries. Fischer et al [33] systematically reviewed the literature on GM crops in agriculture and clarified the country rankings based on the amount, in millions of hectares, of GM crops planted and their appearance in the academic literature: Japan is not included among the top 20 countries in the world. Therefore, Japanese companies' incentives to invent GM crop technologies were relatively low compared to those of companies in other countries.…”
Section: Foodstuff and Agriculture Technologymentioning
confidence: 99%
“…Several scholars [7,32,42,43] as well as an increasing number of governments, international organisations and treaties [44][45][46][47] have noted the importance of incorporating socio-economic aspects in the assessment of GMOs and for this, the urgent need for grounded empirical research. Furthermore, it has been proposed that such empirical work should take into account the "in-context-trajectory" of modern biotechnologies [35].…”
Section: Introductionmentioning
confidence: 99%
“…While approaches to governance have largely been restricted to regulation through a technical assessment of risks to human health and the environment, resistance to the commercialisation of genetically modified organisms (GMOs) stems from a wide spectrum of concerns, covering issues well beyond the scope of risk assessment [1][2][3][4]. These concerns refer, for example, to (a) the socio-economic impacts of GMOs [5][6][7]; (b) the loss of freedom of choice for non-GM producers and consumers [8][9][10][11]; (c) the increasing concentration of power and capital in the hands of ever fewer social actors [12]; (d) the widespread implementation of patents and intellectual property rights to control the development and distribution of varieties [13][14][15][16][17][18]; (e) the failure to account for the significance of scientific uncertainties, paradigms and values in the development of knowledge [19][20][21][22][23]; (f) the domineering or hubristic relationship between humans and nature that GMOs perpetuate [24,25]; and (g) competing narratives of development and diverging visions for the role of the bioeconomy and the future of agriculture [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%